(3GdBKGQ h GdYdGL aj GdGbJUGO GdGSdGejs - (3YjSi(B, (3Ndjajs ((3YeGf(B:s (3OGQ GdfaGFS(B,s, 2011)
(3eONd YGe ddfbhO aj GdGbJUGO GdhVYj h GdGbJUGO GdGSdGej , bjeI GdfbhO h JbdHGJgG , BKGQ GdJZjQGJ aj bjeI GdfbhO , YdGL BKGQ GdJZjQGJ aj bjeI GdfbhO aj GdGbJUGO GdGSdGej , (B.s
(3eQGLY U(B.243s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdfbhOs